Making Headway for Discussions About Concussions: Experiences of Former High School and Collegiate Student-Athletes - Oddo, Anthony; O'Conor, Ellen; Shore, Sarah; Piraino, Mary; Gibney, Kyla; Tsao, Jack; Stanfill, Ansley Grimes (Frontiers in Neurology, 2019)
In order to better understand how to identify and treat student-athletes who experience concussions, better insight into reporting behavior of athletes is needed. This study aims to identify information influencing athletes’ attitudes towards reporting their concussions and the perceived trajectory of their recovery both athletically and academically. Twenty-five former high school and collegiate athletes who experienced concussions in a wide variety of sports, organizational levels, and time periods gave insight through structured, qualitative interviews. A number of factors regarding education about concussions, proper diagnosis of concussions, and motivational pressures within high school and collegiate athletics were assessed. Eight major themes were identified regarding the participants’ experiences with sport-related concussion: optimism bias, invisibility of the injury, diagnostic barriers, desire to play, external support and pressures, uncertainty of long-term prognosis, generational factors, and protection of future athletes. Our findings support that underreporting of concussions among those players interviewed is related to misperceived risk, lack of education, and a struggle between internal and external pressures to play through injury. However, those who did seek medical and academic support, often did receive the necessary aid.